The Effectiveness of Financial Planning on the Performance of the Realization of Village Funds: A Study from Palupi Village, Palu City, Indonesia - Ananda, Mutiara Dea; Kasim, Muhammad Yunus; Kadang , Juliana; Fera , F. (Manunggal Halim Jaya, 2025)
This study aims to analyze the effectiveness of financial planning on the performance of the realization of urban village funds in Palupi Village, Palu City, in 2022-2024. The research method used is descriptive qualitative, utilizing secondary data in annual cash reports, village budgets, and realization of village funds. Results showed that budget realization reached 100% effectiveness in 2022 and 2023 but decreased to 91.5% in 2024 due to budget reallocation for other urgent priorities. The budget allocation shows the main focus on community empowerment activities, which reached 87.3% of the total budget in 2024. An evaluation based on agency theory indicates that the local government, as an agent, has tried to meet the community's needs as the principal. However, community participation in planning still needs to be improved. This research recommends increasing community participation and improving program implementation distribution to support the accountability and effectiveness of Village fund management. With these steps, it is expected that the management of urban village funds can support sustainable development and optimally improve community welfare.